Management of Pre-Partum Cervico-Vaginal Prolapse in aMurrah Buffalo - Verma, Sanjeev Kumar; Kumar, Rajesh; Jaiswal, Sonu; Verma, Abhishek Kumar; Sushant , S Daund (The Indian Journal of Animal Reproduction, 2022)
A 9 months pregnant Murrah buffalo with cervico-vaginal prolapse was presented and it was treated by epidural anaesthesia along with rope truss technique followed by administration of Ceftiofur sodium @ 2.2mg/kg IM for 5 days to prevent secondary infection and herbal remedies arjun bark and hadjod.  The case was recovered uneventfully.
Keywords: Cervico-vaginal prolapse; Herbal remedies; Murrah; buffalo